Much more than an introduction to the language-specific lexical semantics - Igor Marko Gligorić (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave)
An exceptional contribution to Croatian linguistics, Slavistics, and undoubtedly linguistics in general, was published by Matrix Croatica (Matica Hrvatska) in 2024. The book, Introduction to Lexical Semantics of the Croatian Language (Uvod u leksičku semantiku hrvatskoga jezika) by Tatjana Pišković, currently an associate professor at the Department of Croatian Language at the Faculty of Humanities and Social Sciences, University of Zagreb, represents a landmark achievement. The manuscript was reviewed by three distinguished linguists – Maja Bratanić, Branimir Belaj, and Ida Raffaelli – all esteemed figures in their fields. This book cannot be simply categorized as a scientific monograph or a university textbook on lexical semantics, as its scope – both in depth and broadness of the approach – surpasses such classifications, moving toward an encyclopaedic treatment of the central topic.